Obstructive Sleep Apnea and Other Vascular Risk factors' Impact on Non‐Motor Symptoms in Parkinson's Disease. Issue 6 (6th July 2022) - Meira, Bruna; Fernandes, Marco; Salavisa, Manuel; Saraiva, Marlene; Conceição, Laurete; Borbinha, Cláudia; Ladeira, Filipa; Marto, João Pedro; Barbosa, Raquel; Mendonça, Marcelo; Bugalho, Paulo
ABSTRACT: Background: Previous studies revealed an association between vascular comorbidities and obstructive sleep apnea (OSA) and the severity of motor and cognitive symptoms in Parkinson's disease (PD). However, there is a lack of studies assessing the entire spectrum of non‐motor symptoms (NMS). Objective: To investigate the relationship between vascular comorbidities and NMS in PD patients. Methods: Patients were assessed at baseline and 4 years later with the Non‐Motor Symptom Assessment Scale, Parkinson's Psychosis Questionnaire, Unified Parkinson's Disease Rating Scale (UPDRS), Montreal Cognitive Assessment, and Apathy scale. After tetrachoric correlation matrix, we conducted linear regression models (adjusted for age, gender, disease duration, and UPDRS‐III) to investigate the relationship between vascular comorbidities and NMS. Results: In 73 PD patients, (mean disease duration 7.1 [5.3]), 57% had hypertension, 44% body mass index >25, 44% elevated cholesterol, 15% diabetes mellitus, 15% OSA, 14% cigarette‐smoking history, 8% prior stroke, and 8% coronary disease. Cognition, psychotic symptoms, apathy, urinary function, and miscellaneous domains significantly worsened at the 4‐year follow‐up. OSA was significantly associated with higher severity of hallucinations/illusions at baseline and with a more severe deterioration of attention/memory, psychotic symptoms, and apathetic mood at the 4‐year follow‐up. At baseline, but not at follow‐up, hypertension was negatively associated with miscellaneous domain scores and coronary disease with autonomic function scores (gastrointestinal tract and urinary function domains). Conclusion: Among PD‐associated comorbidities, OSA was the main factor of decline. In addition to cognitive impairment, OSA might also potentially worsen psychotic symptoms and apathy. Treatment of OSA could be a strategy to improve these important NMS.